(untitled) (Patrimônio e Memória, 2018)
Disasters have been affecting several municipalities listed as cultural heritage sites, as highlighted by the media stories of the 2010 January floods in São Luiz do Paraitinga city, São Paulo state. This paper shared some findings related to two phases of research. The first phase occurred from January 2010 to June 2013, when of the authors studied the long term disaster recovery process. The second phase was developed from October 2014 to October 2016, when an educational project was run to create intergenerational capacities of disaster risk prevention, articulating the early warning system and educational sectors. The findings denote the need of strengthening the linkages between cultural heritage sector and disaster risk prevention.